Gottfried Konecny: The photogrammetric and remote sensing trend setter. Issue 1 (2nd January 2021) - Jacobsen, Karsten
PREFACE: There are various publications on the 90 th birthday of Gottfried Konecny. His involvement in the International Society for Photogrammetry and Remote Sensing (ISPRS) is particularly described by others. Here, his forward-oriented impulses in research and development at the former Institute for Photogrammetry and Engineering Survey of the (Technical) University of Hannover, today Institute for Photogrammetry and Geoinformation, Leibniz University Hannover, and some of his activities supporting developing and other countries by given short-term courses are highlighted. Gottfried Konecny was always one of the first in pushing new technologies. With the analytical plotter AP/C-3, he introduced analytical photogrammetry in Germany. Based on his experience with this not really operational version, he induced the company Zeiss to develop the first really operational analytical plotter Planicomp, which resulted in the end of analog photogrammetric devices and their limitations. At the invitation of Gilbert Hobrough, a mainly hardware-based image correlator was developed for the AP/C-3 in Hannover which anticipated many of today's applications. Gottfried Konecny initiated remote sensing in Germany. Based on his proposal with the Metric Camera Flight on Spacelab, the then highest resolution civil stereoscopic space images available were generated. Despite limited computer performance at his institute, a digital stereo plotter was developed, using hardware components from the cooperating Swedish company Context Vision, long before digital stereo workstations with increased and affordable computer capacity were possible. Also, in the area of GIS, he too, pushed development in collaboration with companies and administrations. Shortly before the end of his time as head of the institute, and more so after he became emeritus professor, he started a series of educational workshops, particularly in developing countries, but also other countries, to support the development of photogrammetry, remote sensing and GIS. He promoted the use of space imagery for mapping to improve the situation of poorly updated topographic maps.